A method for preparing nano-sized MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern and its application
By using NaOH and NH4HCO3 in the bitter brine to convert Mg2+ into MgCO3·3H2O whiskers, the problem of low magnesium resource utilization efficiency in the bitter brine was solved, and MgCO3·3H2O whiskers with high aspect ratio and fine diameter were prepared, which significantly improved its application performance in epoxy resin.
Patent Information
- Application Number
- CN202410582302.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-05-11
AI Technical Summary
The prior art is difficult to effectively utilize the magnesium resources in bitter brine, and it is difficult to prepare MgCO3·3H2O whiskers with finer diameters and higher aspect ratios, which affects their application in the field of polymer material additives.
Using bitter brine as the raw material, Mg2+ is converted into Mg(OH)2 intermediate by adding solid NaOH, and after dispersing in water, NH4HCO3 and sodium dodecyl sulfate (SDS) are added. By slowly decomposing Mg(OH)2, CO32- is released, and under the action of SDS, MgCO3·3H2O whiskers with a diameter of 55-65 are generated with an aspect ratio of 55-65.
Efficient extraction and conversion of Mg2+ in bitter brine was achieved, and MgCO3·3H2O whiskers with a diameter of 500-700 nm and an aspect ratio of 55-65 were prepared, which significantly improved its mechanical properties and flame retardant properties in epoxy resin modification.
Smart Images

Figure CN118497898B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of nanometer-diameter high aspect ratio MgCO3·3H2O whiskers by indirect mineralization of CO2 with bittern and the field of polymer material additives, and specifically to a method for preparing nanometer-level high aspect ratio MgCO3·3H2O whiskers by indirect mineralization of CO2 with bittern and application thereof. Background Art
[0002] Brine is the byproduct mother liquor after seawater salt production. It contains rich inorganic resources and has extremely high utilization value. At present, the comprehensive utilization of bittern needs to go through three processes in sequence: (1) producing KCl by brine mixing method; (2) producing Br2 by air blowing method; (3) producing MgCl2 by crystallization method. However, the resource utilization rate of this process is not high, the energy consumption is high, the equipment requirements are strict, and the product added value is low. The direct discharge of a large amount of high-salinity bittern may lead to ecological imbalance in coastal waters and cause serious waste of resources. Therefore, realizing the efficient and economic utilization of bittern is an urgent issue in the development of marine chemical industry. Mg 2+ It is the ion with the highest content in bittern, with a concentration of about 2.29 mol / L. 2+ Extracting and converting all of them into high value-added materials will simplify the subsequent separation process of other salts and create considerable economic value. Therefore, the key issue in the efficient utilization of bittern resources lies in how to utilize the magnesium resources rich in bittern.
[0003] MgCO3·3H2O whiskers are a new type of whisker material that has emerged in recent years. They have the advantages of complete crystal development, high strength, light weight, and a wide range of pyrolysis temperatures. They are widely used in rubber filling, engineering plastic filling, sealants, and flame retardant coatings. Kloprogge (Journal of Materials Science, 2003, 22, 825–829) et al. used MgCl2·6H2O and Na2CO3 as raw materials, reacted at 50°C for 10 minutes, and aged for 5 days to obtain needle-shaped MgCO3·3H2O with a diameter of about 7 μm and an aspect ratio of about 50. Yang (Advanced Powder Technology, 2013, 24, 585–592) et al. used MgCl2 and NaHCO3 as raw materials and sodium dodecyl sulfate (SDS) as a crystal control agent to prepare MgCO3·3H2O whiskers with a diameter of about 5 μm and an aspect ratio of 18–45. Wang Yanxia (Inorganic Salt Industry, 2020, 52, 5, 22–26) et al. used MgCl2·6H2O and NH4HCO3 as raw materials and CH3COONa·3H2O as a crystal form controller to prepare MgCO3·3H2O whiskers with a diameter of about 1.5 μm and an aspect ratio of 30. Geng (Journal of CO2 Utilization 2020, 42, 101307) et al. used MgSO4 as raw material, (NH4)2CO3 as a precipitant, and SDS as a crystal form controller to prepare MgCO3·3H2O whiskers with a diameter of 1 μm and an aspect ratio of 40. Although the above work has prepared MgCO3·3H2O whiskers with whisker morphology, they all use chemical reagents as raw materials, which are relatively expensive. In addition, due to the direct precipitation reaction of magnesium salts and carbonates, it is difficult to effectively control the supersaturation. The diameter of the synthesized products is at the micron level and the aspect ratio is not high, which is difficult to meet the needs of practical applications. At the same time, the mother liquor after the reaction is not effectively treated. Therefore, how to economically and greenly prepare MgCO3·3H2O whiskers with finer diameters and higher aspect ratios is of great significance for practical applications. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a method and application of bittern to indirectly mineralize CO2 to prepare nano-scale MgCO3·3H2O whiskers with high aspect ratio. The present invention uses bittern as raw material, and by adding solid NaOH, Mg contained in bittern is removed. 2+ All of them are converted into Mg(OH)2 intermediates, which are then dispersed in water, and NH4HCO3 reagent is added to them. + Slowly decomposes Mg(OH)2 and releases CO3 2- The properties of the solution can effectively control the supersaturation of the solution and release Mg 2+ and CO32- Under the action of SDS, high aspect ratio MgCO3·3H2O whiskers with a diameter of nanometer level and an aspect ratio of 55 to 65 are generated.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0007] Bitter brine is used as raw material, and soluble alkali and Mg(OH)2 seed crystals are added to obtain Mg(OH)2 intermediate. Soluble alkali is added to convert the Mg contained in the bitter brine into 2+ All of them are converted into Mg(OH)2 intermediates, and the addition of Mg(OH)2 seeds improves the filtration performance of the Mg(OH)2 intermediates;
[0008] The Mg(OH)2 intermediate is dispersed in water, NH4HCO3 and a crystal control agent sodium dodecyl sulfate (SDS) are added to obtain a mixed solution, and after stirring and reacting, nano-scale high aspect ratio MgCO3·3H2O whiskers can be obtained. + Slowly decomposes Mg(OH)2 and releases CO3 2- The properties of the solution can effectively control the supersaturation of the solution and release Mg 2+ and CO3 2- Under the action of SDS, high aspect ratio MgCO3·3H2O whiskers with a diameter of nanometer level and an aspect ratio of 55 to 65 are generated.
[0009] In a preferred embodiment of the present invention, the concentration of sodium dodecyl sulfate in the mixed solution is 2-4 g / L, SDS is dissolved in water, and CH3(CH2) is ionized. 11 –OSO3 - ,CH3(CH2) 11 –OSO3 - It is an asymmetric ionic structure and has a polar hydrophilic group – OSO3 - and non-polar hydrophobic groups CH3(CH2) 11 –,Mg 2+ As the active center on the surface of MgCO3·3H2O whiskers, CH3(CH2) generated by SDS dissolution 11 –OSO3 - Combined in a complexing manner, non-polar hydrophobic group CH3(CH2) 11 – Facing the liquid phase, water is expelled, and the radial growth of the whiskers is inhibited, thereby forming whisker materials with a high aspect ratio. However, the addition of too much SDS will affect the supersaturation of the solution, form a micelle effect, affect the nucleation and growth of the crystals, and thus reduce the aspect ratio of the whiskers.
[0010] In a preferred embodiment of the present invention, the stirring reaction time is 45 to 75 minutes, and the reaction temperature is 20 to 30°C.
[0011] In a preferred embodiment of the present invention, the soluble alkali is selected from one of NaOH and KOH, and the Mg in the bittern is 2+ With OH in soluble alkali - The molar ratio of Mg in bittern is 1:2. After adding soluble alkali, the 2+ All converted, utilization rate is 100%.
[0012] In a preferred embodiment of the present invention, the molar ratio of the NH4HCO3 to the Mg(OH)2 intermediate is 2:1.
[0013] In a preferred embodiment of the present invention, the concentration of NH4HCO3 is 1 to 3 mol / L.
[0014] In a preferred embodiment of the present invention, the stirring speed is 150-300 r / min.
[0015] In a preferred embodiment of the present invention, the amount of Mg(OH)2 seed crystals added is 0 to 10% of the total mass of theoretically generated Mg(OH)2.
[0016] Another object of the present invention is to provide a MgCO3·3H2O whisker prepared by any of the preparation methods described above, wherein the diameter of the MgCO3·3H2O whisker is 500-700nm and the aspect ratio is 55-65.
[0017] The third object of the present invention is to provide an application of the above-mentioned MgCO3·3H2O whisker in epoxy resin modification.
[0018] The application method is as follows: fully dispersing the MgCO3·3H2O whisker in anhydrous ethanol, adding it into epoxy resin and stirring it thoroughly, heating to volatilize the anhydrous ethanol, and then adding epoxy resin curing agent to form a MgCO3·3H2O whisker / epoxy resin composite material (MEP).
[0019] In a preferred embodiment of the present invention, the volatilization temperature of anhydrous ethanol is 80-100° C., and the mass ratio of epoxy resin to epoxy resin curing agent is 80-100:10-30.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention uses bittern as raw material and completely extracts Mg contained in bittern in two steps. 2+The MgCO3·3H2O whiskers were further synthesized and the Mg was completely extracted by solid NaOH. 2+ ,Mg 2+ The utilization rate is 100%, and the bittern is not diluted, which has no adverse effect on the subsequent separation of other salts. The property of NH4HCO3 to slowly decompose Mg(OH)2 is used to effectively control the supersaturation of the solution. Under the action of the crystal form control agent sodium dodecyl sulfate, MgCO3·3H2O whiskers with a diameter of nanometers and an aspect ratio of 55 to 65 are prepared. The mother liquor after the reaction is ammonia water, which can reabsorb CO2 to prepare NH4HCO3, forming a new process for indirectly mineralizing CO2 from bittern to prepare nanometer-level high aspect ratio MgCO3·3H2O whiskers.
[0022] 2. The diameter of the MgCO3·3H2O whiskers prepared by the present invention is 500-700 nm, and the aspect ratio is 55-65, while the diameter of the MgCO3·3H2O whiskers prepared by the prior art is at the micron level, and the aspect ratio is 50 or less. It can be seen that the method of the present invention can significantly reduce the diameter of the MgCO3·3H2O whiskers and increase the aspect ratio of the MgCO3·3H2O whiskers.
[0023] 3. The MgCO3·3H2O whiskers prepared by the present invention are used to modify epoxy resin. When the addition amount of MgCO3·3H2O is 6wt%, the tensile fracture stress of the epoxy resin is increased from 31.21MPa to 59.51MPa, and the bending strength is increased from 44.41MPa to 97.13MPa. In addition, the addition of MgCO3·3H2O whiskers has a significant effect on improving the flame retardant properties of epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The XRD spectrum of the MgCO3·3H2O whisker prepared in Example 2 of the present invention;
[0025] Figure 2 This is a SEM image of the MgCO3·3H2O whisker prepared in Example 2 of the present invention;
[0026] Figure 3 The XRD spectrum and SEM image of the product prepared in Comparative Example 1 of the present invention;
[0027] Figure 4 The XRD spectrum and SEM image of the product prepared in Comparative Example 2 of the present invention;
[0028] Figure 5 The XRD spectrum and SEM image of the product prepared in Comparative Example 3 of the present invention;
[0029] Figure 6 The XRD spectrum and SEM image of the product prepared in Comparative Example 4 of the present invention;
[0030] Figure 7 The XRD spectrum and SEM image of the product prepared in Comparative Example 5 of the present invention;
[0031] Figure 8 The mechanical properties of epoxy resin and MEP added in Example 2 are compared;
[0032] Fig. 9 Comparison of the flame retardant properties of epoxy resin and MEP with Example 2 added. DETAILED DESCRIPTION
[0033] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0035] Example 1
[0036] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0037] (1) mixing solid NaOH with bittern, stirring evenly for 30 min at room temperature, and filtering to obtain Mg(OH)2 intermediate;
[0038] Among them, Mg in bittern 2+ The molar ratio with NaOH is 1:2.
[0039] (2) the Mg(OH)2 intermediate obtained in step (1) is uniformly dispersed in distilled water, and a 2 mol / L NH4HCO3 solution is added, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and sodium dodecyl sulfate (SDS) is added to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0040] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0041] Example 2
[0042] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0043] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0044] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0045] (2) the Mg(OH)2 intermediate obtained in step (1) is uniformly dispersed in distilled water, and a 2 mol / L NH4HCO3 solution is added, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and SDS is added to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0046] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0047] Example 3
[0048] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0049] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0050] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 10wt% of the total amount of Mg(OH)2 produced theoretically;
[0051] (2) the Mg(OH)2 intermediate obtained in step (1) is uniformly dispersed in distilled water, and a 2 mol / L NH4HCO3 solution is added, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and SDS is added to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0052] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0053] Example 4
[0054] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0055] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0056] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0057] (2) uniformly dispersing the Mg(OH)2 intermediate obtained in step (1) in distilled water, adding a 2 mol / L NH4HCO3 solution, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and then adding SDS to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 2 g / L;
[0058] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0059] Example 5
[0060] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0061] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0062] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0063] (2) the Mg(OH)2 intermediate obtained in step (1) is uniformly dispersed in distilled water, a 2 mol / L NH4HCO3 solution is added, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and SDS is added to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 4 g / L;
[0064] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0065] Example 6
[0066] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0067] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0068] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0069] (2) the Mg(OH)2 intermediate obtained in step (1) is uniformly dispersed in distilled water, and a 2 mol / L NH4HCO3 solution is added, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and SDS is added to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0070] (3) The mixed solution obtained in step (2) was stirred at 20° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0071] Example 7
[0072] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0073] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0074] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0075] (2) the Mg(OH)2 intermediate obtained in step (1) is uniformly dispersed in distilled water, and a 2 mol / L NH4HCO3 solution is added, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and SDS is added to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0076] (3) The mixed solution obtained in step (2) was stirred at 30° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0077] Example 8
[0078] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0079] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0080] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0081] (2) the Mg(OH)2 intermediate obtained in step (1) is uniformly dispersed in distilled water, and a 1 mol / L NH4HCO3 solution is added, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and SDS is added to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0082] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 200 r / min for 60 min to obtain MgCO 3 · 3H 2 O whiskers.
[0083] Example 9
[0084] A method for preparing nano-scale MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern comprises the following steps:
[0085] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0086] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0087] (2) uniformly dispersing the Mg(OH)2 intermediate obtained in step (1) in distilled water, adding a 3 mol / L NH4HCO3 solution, wherein the molar ratio of NH4HCO3 to the Mg(OH)2 intermediate is 2:1, and then adding SDS to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0088] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 300 r / min for 75 min to obtain MgCO 3 · 3H 2 O whiskers.
[0089] Comparative Example 1
[0090] A method for preparing MgCO3·3H2O whiskers comprises the following steps:
[0091] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0092] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0093] (2) uniformly dispersing the Mg(OH)2 intermediate obtained in step (1) in distilled water, adding NH4HCO3 solution, wherein the molar ratio of NH4HCO3 to Mg(OH)2 intermediate is 2:1, and then adding SDS to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 0 g / L;
[0094] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0095] Comparative Example 2
[0096] A method for preparing MgCO3·3H2O whiskers comprises the following steps:
[0097] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0098] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0099] (2) uniformly dispersing the Mg(OH)2 intermediate obtained in step (1) in distilled water, adding NH4HCO3 solution, wherein the molar ratio of NH4HCO3 to Mg(OH)2 intermediate is 2:1, and then adding SDS to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 5 g / L;
[0100] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 150 r / min for 45 min to obtain MgCO 3 · 3H 2 O whiskers.
[0101] Comparative Example 3
[0102] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0103] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0104] (2) uniformly dispersing the Mg(OH)2 intermediate obtained in step (1) in distilled water, adding NH4HCO3 solution, wherein the molar ratio of NH4HCO3 to Mg(OH)2 intermediate is 2:1, and then adding SDS to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0105] (3) The mixed solution obtained in step (2) was stirred at 55° C. and a speed of 150 r / min for 45 min to obtain a product.
[0106] Comparative Example 4
[0107] (1) mixing solid NaOH with bittern, adding Mg(OH)2 seed crystals, stirring evenly at room temperature for 30 min, and filtering to obtain a Mg(OH)2 intermediate;
[0108] Among them, Mg in bittern 2+ The molar ratio of Mg(OH)2 to NaOH is 1:2, the Mg(OH)2 seed crystals are homemade in the laboratory, and the added amount is 6wt% of the total amount of Mg(OH)2 produced theoretically;
[0109] (2) uniformly dispersing the Mg(OH)2 intermediate obtained in step (1) in distilled water, adding NH4HCO3 solution, wherein the molar ratio of NH4HCO3 to Mg(OH)2 intermediate is 2:1, and then adding SDS to obtain a mixed solution, wherein the concentration of SDS in the mixed solution is 3 g / L;
[0110] (3) The mixed solution obtained in step (2) was stirred at 25° C. and a speed of 150 r / min for 15 min to obtain a product.
[0111] Comparative Example 5
[0112] (1) Add SDS to the MgCl2 solution and stir for 30 min until the SDS is completely dissolved.
[0113] (2) Rapidly add Na2CO3 solution to the mixed solution obtained in step (1) at 25°C, and stir at a speed of 150 r / min for 45 min to obtain a product.
[0114] Among them, Mg in MgCl2 solution 2+ The concentration is similar to that of the Mg(OH)2 intermediate dispersed in water in Example 1. 2+ The concentration of Na2CO3 solution is consistent with that of NH4HCO3 in Example 1; the Mg in the reaction system 2+ With CO3 2- The molar ratio is 1:1; the concentration of SDS in the mixed solution is 3g / L.
[0115] Application Examples
[0116] The MgCO3·3H2O whiskers prepared in Example 2 are uniformly dispersed in anhydrous ethanol, then added to epoxy resin and uniformly stirred. After the anhydrous ethanol is completely volatilized, the epoxy resin curing agent is added to form a MgCO3·3H2O whisker / epoxy resin composite material (MEP), wherein the addition amount of MgCO3·3H2O whiskers is 6wt%, the volatilization temperature of anhydrous ethanol is 80-100°C, and the mass ratio of epoxy resin to epoxy resin curing agent is 80-100:10-30.
[0117] The preparation methods of Example 1, Examples 3-9 and Example 2 of the present invention are the same, and the only difference is that, when experimental conditions permit, the mass concentration of SDS addition, the amount of seed crystals added, the reaction temperature, the reaction time, and the concentration of NH4HCO3 are changed, but this does not affect the performance of the obtained MgCO3·3H2O whiskers. Therefore, the MgCO3·3H2O whiskers prepared in Example 1 and Examples 3-9 have similar performance to that of Example 2, and can both improve the mechanical properties and flame retardant properties of epoxy resin.
[0118] The following test methods are used in various embodiments of the present invention:
[0119] XRD test was carried out using a D8Focus instrument from Bruker, Germany, to characterize the phase composition of the product. The relevant parameters of the instrument were: CuKα radiation, tube current 200mA, tube voltage 40kV, scanning speed 12° / min, and scanning range 5–70°.
[0120] The SEM test was conducted by the American FEI company, model NovaNanoSEM450, which was mainly used to determine the specific morphology and aspect ratio of MgCO3·3H2O whiskers.
[0121] The mechanical properties test was conducted by Xinsansi (Shanghai) Enterprise Development Co., Ltd. Model CMT6104, which is mainly used to test the mechanical properties of epoxy resin and MEP. The tensile test and bending test were conducted according to GB / T2567-2008. The tensile test sample was a dumbbell strip, and the bending test sample was 80×10×3mm. 3 The instrument parameters are: 10KN sensor, tensile strength test rate is 10mm / min, bending strength test rate is 2mm / min.
[0122] The cone calorimeter test uses the i-Cone model from the British FTT company, which mainly tests the flame retardancy of epoxy resin and MEP. The sample size is 100×100×3mm 3 The test is carried out according to ISO5660-1 national standard, and the radiation intensity is 35kW / m 2 .
[0123] Results Analysis
[0124] The XRD pattern of the MgCO3·3H2O whiskers prepared in Example 2 is as follows: Figure 1 As shown, it can be seen that the synthesized product is pure MgCO3·3H2O.
[0125] The SEM images of the MgCO3·3H2O whiskers prepared in Example 2 are as follows: Figure 2 As shown, the diameter of the synthesized product is 500 nm and the aspect ratio is 65. The MgCO3·3H2O whiskers prepared in other embodiments also exhibit nanoscale high aspect ratio whisker morphology, and the specific diameter and aspect ratio results are shown in Table 1.
[0126] The XRD spectrum and SEM image of MgCO3·3H2O whiskers prepared in Comparative Example 1 are as follows Figure 3 As shown in the figure, XRD results show that the product is pure MgCO3·3H2O. From the SEM image, it can be seen that the diameter of the synthesized product under this condition is significantly thickened to 3.5μm, and the aspect ratio is significantly reduced to 15. This result shows that the addition of SDS has a significant regulatory effect on the morphology of MgCO3·3H2O whiskers.
[0127] Comparative Example 2 The XRD spectrum and SEM image of MgCO3·3H2O whiskers prepared are as follows Figure 4As shown, the XRD results show that the product is pure MgCO3·3H2O. From the SEM image, it can be seen that the diameter of the product synthesized under this condition is about 1.1μm, the aspect ratio is about 20, and it has a bundle-like agglomerated structure.
[0128] SDS dissolves in water and ionizes into CH3(CH2) 11 –OSO3 - ,CH3(CH2) 11 –OSO3 - It is an asymmetric ionic structure and has a polar hydrophilic group – OSO3 - and non-polar hydrophobic groups CH3(CH2) 11 –,Mg 2+ As the active center on the surface of MgCO3·3H2O whiskers, CH3(CH2) generated by SDS dissolution 11 –OSO3 - Combined in a complexing manner, non-polar hydrophobic group CH3(CH2) 11 – Facing the liquid phase, water is expelled, and the radial growth of the whiskers is inhibited, thereby forming whisker materials with a high aspect ratio. However, the addition of too much SDS will affect the supersaturation of the solution, form a micelle effect, affect the nucleation and growth of the crystals, and thus reduce the aspect ratio of the whiskers.
[0129] The XRD pattern and SEM image of the product prepared in Comparative Example 3 are as follows: Figure 5 As shown in Figure 2. XRD results show that the product is not pure MgCO3·3H2O, but also contains some 4MgCO3·4Mg(OH)2·4H2O. The SEM image shows obvious flakes covering the surface of the MgCO3·3H2O whiskers, which indicates that the increase in temperature will cause MgCO3·3H2O to transform into 4MgCO3·4Mg(OH)2·4H2O.
[0130] The XRD pattern and SEM image of the product prepared in Comparative Example 4 are as follows Figure 6 The XRD results show that due to insufficient reaction time, there is unreacted Mg(OH)2 in the product, and the SEM image shows that the product is in an uneven block shape.
[0131] The XRD spectrum and SEM image of MgCO3·3H2O whiskers prepared in Comparative Example 5 are as follows Figure 7As shown, the XRD results show that the product is pure MgCO3·3H2O. The SEM image shows that the diameter of the MgCO3·3H2O whiskers synthesized by this scheme is 2 to 4 μm, and the aspect ratio is 4 to 20. Since the reaction is a direct mixing of a magnesium salt solution and a carbonate solution, the supersaturation of the solution increases rapidly in a very short period of time, resulting in a large number of crystal nuclei, which causes the diameter of the MgCO3·3H2O to become coarser and the aspect ratio to decrease. This shows that the bittern two-step method proposed in the present invention for indirectly mineralizing CO2 to prepare nanoscale MgCO3·3H2O whiskers with a high aspect ratio can significantly control the supersaturation of the solution compared to the scheme of Comparative Example 5, and prepare MgCO3·3H2O with a fine diameter and a high aspect ratio.
[0132] Table 1 Diameter and aspect ratio of MgCO3·3H2O whiskers synthesized in Examples 1-9 and Comparative Examples 1-5
[0133] diameter Aspect Ratio Example 1 500nm 60 Example 2 500nm 65 Example 3 530nm 62 Example 4 550nm 62 Example 5 700nm 55 Example 6 500nm 63 Example 7 680nm 57 Example 8 500nm 65 Example 9 650nm 58 Comparative Example 1 3.5μm 15 Comparative Example 2 1.1μm 20 Comparative Example 3 / / Comparative Example 4 / / Comparative Example 5 2–4 μm 4–20
[0134] The mechanical properties of epoxy resin and MEP prepared in the application example are compared as follows Figure 8 The detailed data comparison is shown in Table 2. After adding MgCO3·3H2O whiskers, the tensile fracture stress and elongation at break of MEP are significantly improved, and the flexural strength and flexural modulus are also significantly improved. This shows that the addition of MgCO3·3H2O whiskers can significantly improve the mechanical properties of epoxy resin.
[0135] Table 2 Comparison of mechanical properties of epoxy resin and MEP prepared by application examples
[0136] Tensile stress at break Elongation at break Bending Strength Flexural modulus Epoxy resin 31.32MPa 7.35% 44.41MPa 206.88MPa MEP 59.51MPa 11.60% 97.13MPa 730.04MPa Δ 90.00%↑ 57.82%↑ 118.71%↑ 252.88%↑
[0137] The flame retardant properties of epoxy resin and MEP prepared in the application example are compared as follows Fig. 9 The detailed data comparison is shown in Table 3. The results show that the flame retardant properties of MEP are significantly improved after adding MgCO3·3H2O whiskers.
[0138] Table 3 Comparison of flame retardant properties of epoxy resin and MEP prepared by application examples
[0139]
[0140] Among them, HRR: heat release rate; THR: total heat release; SPR: smoke generation rate; TSR: cumulative total smoke generation; COP: CO generation rate; CO2P: CO2 generation rate.
[0141] In summary, converting CO2 into carbonate materials through mineralization has the advantages of low cost and high product added value. 2+The extraction of MgCO3·3H2O was combined with the utilization of CO2 to prepare MgCO3·3H2O whiskers, which would be bittern Mg 2+ Therefore, the present invention uses bittern as raw material and completely extracts Mg contained in bittern in two steps. 2+ Converted to Mg(OH)2, further synthesized into MgCO3·3H2O whiskers. Use solid NaOH to completely extract Mg 2+ , and the bittern was not diluted, which had no adverse effect on the subsequent separation of other salts. The property of NH4HCO3 to slowly decompose Mg(OH)2 was utilized to effectively control the supersaturation of the solution, and MgCO3·3H2O whiskers with a diameter of nanometer level and an aspect ratio of 55 to 65 were prepared under the action of SDS. And the mother liquor after the reaction was ammonia water, which could reabsorb CO2 to prepare NH4HCO3, forming a new process for indirectly mineralizing CO2 from bittern to prepare nanometer-level high aspect ratio MgCO3·3H2O whiskers. The MgCO3·3H2O whiskers prepared by the present invention are used for the modification of epoxy resin. When the addition amount of MgCO3·3H2O is 6wt%, the tensile fracture stress of the epoxy resin is increased from 31.21MPa to 59.51MPa, and the bending strength is increased from 44.41MPa to 97.13MPa. In addition, the addition of MgCO3·3H2O whiskers has a significant improvement effect on the flame retardant properties of epoxy resin.
[0142] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0143] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing nano-sized MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern, characterized in that: The following steps are involved: Taking bittern as raw material, adding soluble alkali to it, Mg(OH)2 intermediate is obtained; The Mg(OH)2 intermediate is dispersed in water, NH4HCO3 is added, and NH4 + Decomposes Mg(OH)2 and releases CO3 2- and Mg 2 + , a mixed solution is obtained, and under the action of the crystal form controlling agent sodium dodecyl sulfate, Mg 2+ and CO3 2- The reaction generates nanoscale MgCO3·3H2O whiskers with a high aspect ratio; The mass concentration of the sodium dodecyl sulfate in the mixed solution is 2 to 4 g / L; Mg 2+ and CO3 2- The reaction time is 45-75 minutes, and the reaction temperature is 20-30°C; The soluble alkali is selected from one of NaOH and KOH, and the Mg in the bittern is 2+ With OH in soluble alkali - The molar ratio is 1:
2.
2. The method for preparing nano-sized MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern according to claim 1, characterized in that: The molar ratio of the NH4HCO3 to the Mg(OH)2 intermediate is 2:
1.
3. The method for preparing nano-sized MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern according to claim 1, characterized in that: The molar concentration of NH4HCO3 is 1-3 mol / L.
4. The method for preparing nano-sized MgCO3·3H2O whiskers with high aspect ratio by indirect mineralization of CO2 with bittern according to claim 1, characterized in that: When preparing the Mg(OH)2 intermediate, Mg(OH)2 seed crystals are added to the raw materials, and the mass fraction of the added Mg(OH)2 seed crystals in the total mass of the theoretically generated Mg(OH)2 is ≤10%.
5. A MgCO3·3H2O whisker obtained by the preparation method according to any one of claims 1 to 4, characterized in that: The diameter of the MgCO3·3H2O whisker is 500-700nm, and the aspect ratio is 55-65.
6. Use of the MgCO3·3H2O whisker according to claim 5 in epoxy resin modification, characterized in that: The application method is as follows: the MgCO3·3H2O whisker is mixed with anhydrous ethanol, added into epoxy resin and stirred, heated to volatilize the anhydrous ethanol, and then an epoxy resin curing agent is added to form a MgCO3·3H2O whisker / epoxy resin composite material.
7. The use according to claim 6, characterized in that: The volatilization temperature of anhydrous ethanol is 80-100° C., and the mass ratio of epoxy resin to epoxy resin curing agent is 80-100:10-30.
Citation Information
Patent Citations
Method for preparing basic magnesium chloride whisker from dolomite and bittern
CN101353815A
Method for preparing magnesium carbonate trihydrate crystal whisker by utilizing serpentine
CN102703982A